Seed germination and vigor of passion fruit hybrids - Souto, Antônio Gustavo de Luna; Cremasco, João Paulo Gava; Maitan, Mariana Quintas; Azevedo, Jéssica Laisca Fernanda de; Ribeiro, Mariana Rodrigues; Santos, Carlos Eduardo Magalhães dos (Comunicata Scientiae, 2017)
Most commercial plantations of passion fruit is propagate plants by seed, but germination is irregular, which hinders the growth of seedlings and uniformity, and is connected with the plant genotype. The objective of this study was to evaluate the germination and early growth of passion fruit hybrid seedlings, obtained from different genetic combinations. The hybrids were obtained from the cross between progenies from the breeding program of the Universidade Federal de Viçosa with hybrids of the Empresa Brasileira de Pesquisa Agropecuária and of the Viveiros Flora Brasil. The experimental design was completely randomized with six hybrids, five replicates and fifty seeds per experimental unit. Germination was assessed daily until the 28 days, and at the end of the period it was obtained the mean time germination, emergence speed index, seedling height, the length of shoots and roots, and the individual seedling dry matter (root + shoot)was assessed. Among the passion fruit hybrids evaluated, hybrid HB2 (UFVM0212 × BRS Sol do Cerrado) showed the highest germination and seedling biometric values and might be a genotype with potential for breeding programs for seed quality. The specific combining ability of parents can influence the quality of seeds and the vigor of passion fruit seedlings. A factor must be considered is the correct choice of maternal and paternal parents, since they influence the quality of seeds.